Pengaruh Budaya Kerja dan Kemampuan Terhadap Komitmen Pegawai Dinas Kesehatan Kabupaten Empat Lawang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2021)
ABSTRACTThe research, entitled the influence of work culture and ability on the commitment of the employees of the Empat Lawang District Health Office, aims to determine whether there is an influence of work culture and ability on the commitment of the Empat Lawang District Health Office employees partially and together. The sampling technique was saturated sampling (census) with a total of 40 respondents. The method used is quantitative method with statistical test. Data collection techniques were carried out using questionnaires and documentation. The data analysis techniques used were instrument test and classical assumption test. The t-test obtained a sig value of 0.000